Locating Thunder Source Using a Large-Aperture Micro-Barometer Array - Rusz, Jan; Chum, Jaroslav; Baše, Jiří (Frontiers in Earth Science, 2021)
Lightning generates sound waves across a wide range of frequencies, including infrasonic waves below 20 Hz. Source mechanism for these low frequency pulses is still area for debate. Infrasound pulses detected after rapid changes of electrostatic field during the thunderstorm activity were analyzed. The measurements were done by large aperture array of absolute microbarometers located in the Western part of the Czech Republic. Distances between four measuring sites are in the range of 4–10 km. The infrasound source position was calculated from time delays between the rapid change of electrostatic field and infrasound signal arrival to the individual microbarometers assuming propagation of spherical waves from the source. Only cases with a sufficient signal-to-noise ratio on all four microbarometers were analyzed. The variation of sound speed with height due to temperature height profile was taken into account. For most of the analyzed cases, the calculated infrasound source position corresponds to the lightning location determined by European lightning detection network (EUCLID). The calculated height of infrasound source is most often 3–5 km.